Intraosseous autoserotherapy of lumbar osteochondrosis - V. I. Perveyev; G. A. Sukhanova; I. V. Perveyev; M. I. Avakov (Бюллетень сибирской медицины, 2004)
138 patients with lumbar osteochondrosis (LOC) in age of 32—73 years with apparent pain syndrome and neurologic manifestations have been examined, these patients have received 316 autoserotherapy (AST) procedures. It has been revealed that in LOC patients a disturbance of coagulation blood properties and micricirculation as well as immunoglobulin M and G concentration increase, circulating immune complexes (CIC) increase, increase of kinin activity by more than 2 times had taken place. Course of AST procedures permits to decrease the blood coagulability and kallikrein activity almost up to the norm, to improve the microcirculation (by capillaroscopy data), to eliminate the disimmunoglobulinemia that is accompanied by the decrease of disease symptom evidence. Inclusion of AST procedures in LOC treatment complex decreases in short time the intensity of lumbar pains, decreases the hospitalization duration by (9,4 ± 1,1) days, increases the remission duration as compared to the control patient group that received the traditional treatment only.